2020
DOI: 10.1142/s2424786320500139
|View full text |Cite
|
Sign up to set email alerts
|

The modified binomial options pricing model and the revised replicating portfolio approach with the concept of sustainability options

Abstract: This paper discusses whether the project investment can develop the decision-making for the concept of sustainability options. The conventional net present value (NPV) approach assesses whether the project investment should be implemented, and develops the evaluation criteria of implementing sustainability costs from the modified binomial options pricing model (BOPM) and the revised replicating portfolio approach. It treats options premium value and the replicating portfolio approach (RPA) value as the objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Different models have been developed considering binomial pricing strategies. A few instances of such studies include a flexible binomial option pricing model (Lin et al 2020 ), and a case for using real options’ pricing analysis to evaluate information technology project investments (Cruz Rambaud and Sánchez Pérez 2016 ). However, it has been analyzed and found that binomial pricing models are suitable for developing a simple pricing strategy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Different models have been developed considering binomial pricing strategies. A few instances of such studies include a flexible binomial option pricing model (Lin et al 2020 ), and a case for using real options’ pricing analysis to evaluate information technology project investments (Cruz Rambaud and Sánchez Pérez 2016 ). However, it has been analyzed and found that binomial pricing models are suitable for developing a simple pricing strategy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%